Electromechanical transient processes during supply voltage changing in the system of polymer insulation covering of the current-carrying core of ultra high voltage cables - Zolotaryov, V.M.; Shcherba, M.A.; Belyanin, R.V.; Mygushchenko, R.P; Korzhov, I.M. (Електротехніка і електромеханіка, 2018)
Aim. The article is devoted to the analysis of the electromechanical transient processes in a system of three frequency-controlled
electric drives based on asynchronous motors that control current-carrying core motion, as well as to the study of the effect of
such processes on the modes applying three-layer polymer insulation to the current-carrying core. Technique. The study was conducted based on the concepts of electromechanics, electromagnetic field theory, mathematical physics, mathematical modeling.
Results. A mathematical model has been developed to analyze transients in an electromechanical system consisting of three frequency-controlled electric drives providing current-carrying core motion of ultra-high voltage cables in an inclined extrusion
line. The coordination of the electromechanical parameters of the system drives has been carried out and the permissible changes
in the supply voltage at the limiting mass while moving current-carrying core of ultra-high voltage cables with applied polymer
insulation have been estimated. Scientific novelty. For the first time it is determined that with the limiting mass of the currentcarrying core, the electromechanical system allows to stabilize the current-carrying core speed with the required accuracy at
short-term decreases in the supply voltage by no more than 27 % of its amplitude value. It is also shown that this system is resistant to short-term increases in voltage by 32 % for 0.2 s. Practical significance. Using the developed model, it is possible to calculate the change in the configuration and speed of the slack current-carrying core when applying polymer insulation, depending
on the specific mass of the current-carrying core per unit length, its tension at the bottom, the torque of the traction motor and the
supply voltage to achieve stable operation of the system and accurate working of the set parameters. Цель. Целью статьи является проведение анализа электромеханических переходных процессов в системе из трех
частотно регулируемых электроприводов на базе асинхронных двигателей, которые управляют движением токопроводящей жилы, а также исследование влияния таких процессов на режимы нанесения на жилу трехслойной полимерной изоляции. Методика. Для проведения исследований использовались положения электромеханики, теории
электромагнитного поля, математической физики, математического моделирования. Результаты. Разработана
математическая модель, позволяющая анализировать переходные процессы в электромеханической системе, состоящей из трех частотно регулируемых электроприводов, обеспечивающих движение токопроводящей жилы сверхвысоковольтного кабеля в наклонной экструзионной линии. Проведено согласование электромеханических параметров
приводов системы и выполнена оценка допустимых изменений напряжения питающей сети при предельной массе
движущейся жилы сверхвысоковольтного кабеля с нанесённой на нее полимерной изоляцией. Научная новизна. Впервые определено, что при предельной массе токопроводящей жилы электромеханическая система позволяет стабилизировать скорость перемещения жилы с необходимой точностью при кратковременных уменьшениях питающего
напряжения не более чем на 27 % от его амплитудного значения. Также показано, что данная система является устойчивой к кратковременному увеличению напряжения на 32 % в течение 0,2 с. Практическое значение. Использование разработанной модели позволяет рассчитывать изменение конфигурации и скорости движения провисающей
токопроводящей жилы при нанесении на нее полимерной изоляции, в зависимости от удельной массы жилы на единицу длины, ее натяжения в нижней точке, момента тягового электродвигателя и величины питающего напряжения для достижения стабильной работы системы и точной отработки заданных параметров